ANALISIS KESALAHAN BERBAHASA DALAM KARANGAN SEDERHANA MAHASISWA JURUSAN PENDIDIKAN BAHASA JERMAN FBS UNM - Al-Ilmullah, Syarifah Fatimah; Anwar, Muhammad (STILISTIKA, 2012)
ANALISIS KESALAHAN BERBAHASA DALAM KARANGAN SEDERHANA MAHASISWA JURUSAN PENDIDIKANBAHASA JERMAN FBS UNM  Syarifah Fatimah Al-Ilmullah dan Muhammad AnwarJurusan Pendidikan Bahasa Jerman Fakultas bahasa dan Seni Universitas Negeri Malang Abstract This study aimed to: 1) find the types of errors found in a simplebouquet of Education Department of German students UNM FBSand 2) to overcome the mistakes of the German Language Education Department students FBS UNM in writing a simpleessay. The method used is analytical descriptive method that isinterpretive. In it covered a business of describing, recording,analyzing and interpreting linguistic phenomena that occur duringthe research conducted. This study aimed to search for information that can be used in making decisions. Results anddiscussion are: 1) in a simple bouquet of students affected by theIndonesian acquisition of German language acquisition. It is foundon a simple student essays. Indonesian influence on the Germanlanguage occurs at the level of morphology, syntax, and lexicon, 2) global error occurs because the wrong choice of words.Student exchange between the type of words to one another, orbetween similar words in a sentence. This shows that the mastery of vocabulary Jerrnan students is still low; 3) intralingual errorsthat occur in a simple student essays are generally caused byexcessive leveling, This error occurs on the morphology andsome syntax errors, 4) The mistake most often occurs in simpleessays students are errors involving verbs, such as verbconjugation at the level of morphology, placement and correctionsas well as the congruence sub verb Key words: analysis, fault-speaking, a simple bouquet of student